International Symposium on Mathematics, Quantum Theory, and Cryptography Proceedings of MQC 2019 - Takagi, Tsuyoshi; Wakayama, Masato; Tanaka, Keisuke; Kunihiro, Noboru; Kimoto, Kazufumi; Ikematsu, Yasuhiko; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2021)
This open access book presents selected papers from International Symposium on Mathematics, Quantum Theory, and Cryptography (MQC), which was held on September 25-27, 2019 in Fukuoka, Japan. The international symposium MQC addresses the mathematics and quantum theory underlying secure modeling of the post quantum cryptography including e.g. mathematical study of the light-matter interaction models as well as quantum computing. The security of the most widely used RSA cryptosystem is based on the difficulty of factoring large integers. However, in 1994 Shor proposed a quantum polynomial time algorithm for factoring integers, and the RSA cryptosystem is no longer secure in the quantum computing model. This vulnerability has prompted research into post-quantum cryptography using alternative mathematical problems that are secure in the era of quantum computers. In this regard, the National Institute of Standards and Technology (NIST) began to standardizepost-quantum cryptography in 2016. This book is suitable for postgraduate students in mathematics and computer science, as well as for experts in industry working on post-quantum cryptography.
Sustainable Cryptography -- What Kind of Insight Provide Analytical Solutions of Quantum Models? -- Emerging Ultrastrong Coupling between Light and Matter Observed in Circuit Quantum Electrodynamics -- Quantum Random Numbers Generated by a Cloud Superconducting Quantum Computer -- Quantum Factoring Algorithm: Resource Estimation and Survey of Experiments -- A Review of Secret Key Distribution Based on Bounded Observability -- Towards Constructing Fully Homomorphic Encryption without Ciphertext Noise from Group Theory -- Number Theoretic Study in Quantum Interactions -- From the Bloch Sphere to Phase Space Representations with the Gottesman-Kitaev-Preskill Encoding -- A Data Concealing Technique with Random Noise Disturbance and A Restoring Technique for the Concealed Data by Stochastic Process Estimation.
Keywords: Engineering mathematics; Engineering -- Data processing; Data structures (Computer science).; Information theory; Quantum computers; Data protection; Mathematical and Computational Engineering Applications; Data Structures and Information Theory; Quantum Computing; Data and Information Security